CITRA SUREALISME JALANAN: ANALISIS STREET PHOTOGRAPHY KARYA ROY RUBIANTO MELALUI KONSEP HASARD OBJECTIF DAN THE MARVELOUS - Anom Purnomo, Aji Susanto (Institut Seni Indonesia Yogyakarta, 2025)
This study analyzes Roy Rubianto’s street photography in the photo book “INTIP” through the lens of surrealism as conceptualized by Andre Breton in the “Manifesto of Surrealism.” Employing a qualitative descriptive approach, the researcher interprets four selected photographs using Roland Barthes’ “studium” and “punctum” to explore their composition, lighting, and imaginative juxtapositions. The analysis reveals that candid images, captured over 14 years in Jakarta, create new narratives challenging perceptions of reality, embodying Breton’s “hasard objectif” and “The Marvelous.” The study concludes that street photography can enrich artistic discourse by unveiling the surreal in everyday life, offering a unique human perspective in the age of advanced technology. It suggests further exploration of surrealistic imagination in photography to uncover hidden layers of reality.